The corrections - Franzen, Jonathan (London : Fourth Estate, 2010)
The Lamberts - Enid and Alfred and their three grown-up children - are a troubled family living in a troubled age. Alfred is slowly losing his mind to Parkinson's disease. As his condition worsens, and the Lamberts are forced to face the secrets and failures that haunt them, Enid sets her heart on gathering everyone together for one last family Christmas.
Winner of the National Book Award and Winner of the James Tait Black Memorial Prize.
Keywords: Married women -- Fiction; Parkinson's disease -- Patients -- Fiction; Parent and adult child -- Fiction; Middle West -- Fiction